Assessing animal health delivery for tick and tick-borne disease control in smallholder dairy systems of Kenya : an application of new institutional economics - Coetzee, Gerhard (University of Pretoria, 2013)
Thesis (PhD (Veterinary Sciences))--University of Pretoria, 2002.